Large Incisional Hernia in a Mule - Surgical Treatment - Tavares de Moraes, Isadora David; Paiva Nunes, Júlia; Melo Ribeiro, Henrique; Fagundes Araujo, Michaella; Oliveira Costa, Maria Clara; Guimarães Franco, Leandro; Feitosa Noronha Filho, Antônio Dionísio; Queiroz, Paulo José Bastos (Acta Scientiae Veterinariae, 2025)
Background: Incisional hernias (IHs) are surgical complications resulting from failure of abdominal wall closure, allowing protrusion of the viscera without skin rupture. This prevalence of IHs is approximately 18% in equids following celiotomy and may be associated with surgical site infection, suture dehiscence, and increased intra-abdominal pressure. Most IHs require surgical repair via hernioplasty. However, postoperative complications are common. This case report describes a surgical procedure performed to correct a large abdominal IH in a mule. Case: A 12-year-old female mule (Pêga × Mangalarga Marchador), wheiging 368 kg, was attended with a large IH on the ventral midline that developed following an exploratory celiotomy for acute abdominal syndrome treatment. Evaluation of the hernia revealed a hernia ring approximately 35 cm in diameter, partially reducible content, and no signs of active inflammation. Ultrasonography demonstrated the viability of the intestinal loops and absence of adhesions. The surgical treatment included primary hernioplasty without mesh implantation using alternating large-caliber polyamide and polyglycolic acid interrupted sutures. The surgical technique included an elliptical incision, blunt dissection of the hernia sac, debridement of the hernia ring, herniorrhaphy with tension-relieving sutures, and closure of the anatomical layers. Postoperative management included systemic antibiotic therapy with potassium, penicillin, and gentamicin, analgesia with flunixin meglumine, daily wound care, and application of a compressive abdominal bandage. On postoperative day 28, the animal was discharged with recommendations for continued use of a compression belt, strict stall rest for an additional 60 days, and a gradual return to physical activity. After full recovery, satisfactory cosmetic results and a restored quality of life were observed. Seventeen months after discharge, the owner was contacted via a messaging application and reported no recurrence of the hernia and full return of the animal to athletic activities without performance impairment. Discussion: IHs are complications that occur in 6-18% of horses and associated with factors, such as increased intra-abdominal pressure, suture technique failure, infections, and healing disorders. Presently, surgical site infection led to tissue fragility and suture dehiscence, resulting in an incisional hernia. Equids weighing > 300 kg are at a greater risk of complications, as observed in this case. Ultrasonography is essential for surgical planning, because it demonstrates the absence of adhesions and infections. For defect repair, simple interrupted sutures with tension-relieving stitches were used, as this technique reduces ischemia and allows for better distribution of tension along the hernia ring margins. For the suture material, large-caliber polyglycolic acid and polyamide were alternated to ensure sufficient support without excessive tension. Stall rest and abdominal bandaging are crucial for a successful treatment. Herniorrhaphy using simple interrupted sutures with tension-relieving stitches and alternating large-caliber polyglycolic acid and polyamide is a viable option for the treatment of IHs in mules. Keywords: equidae, His, herniorrhaphy, surgery, mule. Título: Hérnia incisional de grandes dimensões em uma mula - tratamento cirúrgico Descritores: equídeos, His, herniorrafia, muar.